The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fmicb.2021.622704
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin Resistance Among XDR ST1 Carbapenem-Resistant Acinetobacter baumannii Clone Expanding in a Teaching Hospital

Abstract: Acinetobacter baumannii is an opportunistic pathogen primarily associated with multidrug-resistant nosocomial infections, for which polymyxins are the last-resort antibiotics. This study investigated carbapenem-resistant A. baumannii strains exhibiting an extensively drug-resistant (XDR) phenotype, including four isolates considered locally pan drug-resistant (LPDR), isolated from inpatients during an outbreak at a teaching hospital in Brazil. ApaI DNA macrorestriction followed by PFGE clustered the strains in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 62 publications
0
13
1
2
Order By: Relevance
“…The emergence of MDR/XDR pathogens over the last decade is dramatically increasing. Many studies have been conducted to magnify the impact of MDR, XDR, and PDR (pan-drug resistance) on strategies and protocols of treatment, especially nosocomial infections caused by A. baumannii [ 27 - 29 ]. Recent developments in the field of antimicrobial drugs are devoted to the use of natural antimicrobial and nanoparticle delivery agents [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of MDR/XDR pathogens over the last decade is dramatically increasing. Many studies have been conducted to magnify the impact of MDR, XDR, and PDR (pan-drug resistance) on strategies and protocols of treatment, especially nosocomial infections caused by A. baumannii [ 27 - 29 ]. Recent developments in the field of antimicrobial drugs are devoted to the use of natural antimicrobial and nanoparticle delivery agents [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the return of polymyxins as effective drugs for the treatment of multidrug-resistant bacterial infections, especially carbapenem-resistant Gram-negative bacterial infections, the emergence of PB-resistant A. baumannii has increased in recent years ( 51 , 52 ). In this study, the antimicrobial effect of PB in combination with antibiotics on the growth of planktonic cells varied on the strains and genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…All six colistin-resistant isolates were resistant to carbapenems and exhibited an XDR phenotype. Recently, colistin-resistant A. baumannii ST1 and ST2 isolates were reported in Brazil and South Africa; the authors also showed that the collected isolates were resistant to carbapenems and exhibited XDR phenotypes (Snyman et al, 2020;Carrasco et al, 2021;Nogbou et al, 2022). The most frequent β-lactamase genes detected in this study were bla OXA−23 , bla NDM−1 , and bla PER−7 .…”
Section: Resistancenodulation-division Adeabc and Adefghmentioning
confidence: 98%